Pengembangan Aplikasi Pembelajaran Pengucapan Bahasa Inggris Berbasis Android Menggunakan Automatic Speech Recognizer (ASR) - Mohammad Chaliffilardhy Syaifuddin; Agi Putra Kharisma; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
English is one of the most spoken languages in the world. English speakers in Indonesia are below the average in the Asian region. This is due to a lack of interest, lack of basic knowledge, a less supportive environment, often forgetting the concepts learned, and no opportunity to learn. In addition, Indonesian people in general have difficulty in speaking English words or sentences. A new learning media is needed to make it easier to learn English pronunciation. This research develops an Android application that is able to assess and learn English pronunciation. This application implements Automatic Speech Recognition (ASR) for assessment features and implements Text To Speech for learning features. The rating and learning of English pronunciation in applications are limited to 10 words, namely gigantic, architecture, enormous, notorious, tiny, fabulous, enough, voracity, prosperity, and failure. Pronouncement assessment results are shown using the terms Perfect, Good, Not Bad, Bad, and Horrible. Perfect shows the highest value and Bad shows the lowest value. Pronunciation learning is implemented by voicing examples of pronunciation for 10 words assessed on the application. Accuracy and usability testing was conducted on 21 students of class XI (eleven) majoring in language. The accuracy testing results 82.38% of the assessment in accordance with the assessment of the English teacher. Usability testing results show 89.73% of users are satisfied with the application interface and appearance.